COMPARATION OF STUDENTS’ ACHIEVEMENT ON THE TOPIC OF LINEAR EQUATION ON TWO VARIABLES AT SMP NEGERI 19 AMBON - Batkormbawa, Vista Dolly; Molle, Juliana Selvina; Ngilawajan, Darma Andreas (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2022)
This research is intended to find out the differences of students’ achievement which taught by using Team Assisted Individualization model and Think Pair Share model. Population of this research are 8th grade students of SMP Negeri 19 Ambon which consists of 10 classes. Research samples are students of class VIII-5 which stated as experiment group I (using TAI model) and students of class VIII-3 which stated as experiment group II (using TPS model). Each experiment group using different learning instruments, especially on students’ worksheets. This research is a quantitative research using posttest only group design. Data of this research is analyzed using t-test which supported by SPSS software version 22.0. Result shows that students group which using Team Assisted Individualization model has better achievement compare to Students on Think Pare Share class